To cleave or not and how? The DNA exonucleases and endonucleases in immunity - Mingjun Lu; Jinghong Wu; Qing Gao; Renjing Jin; Changming An; Teng Ma (Genes and Diseases)
DNA exonucleases and endonucleases are key executors of the genome during many physiological processes. They generate double-stranded DNA by cleaving damaged endogenous or exogenous DNA, triggering the activation of the innate immune pathways such as cGAS-STING-IFN, and enabling the body to produce anti-viral or anti-tumor immune responses. This is of great significance for maintaining the stability of the genome and improving the therapeutic efficacy of tumors. In addition, genomic instability caused by exonuclease mutations contributes to the development of various autoimmune diseases. This review summarizes the DNA exonucleases and endonucleases which have critical functions in immunity and associated diseases.